Analysis of the connection between urban land cover and census districts using geoinformatical methods - Henits, László; Mucsi, László (Acta Geographica Debrecina Landscape & Environment series, 2012)
Remote sensing resources are usually used in research to better understand urban built-up density, spatial structure and the processes of change. Based on results of image segmentation, landscape metrics indexes, texture and pattern may be analyzed beside the spatial changes in urban reflectance. Social processes within the settlement can be analyzed efficiently, although the census data may also be connected to the urban land cover data through geoinformation systems. On the research project different parameters of urban segments, i.e. patch number, mean patch area, total patch area, total patch perimeter, patch density and edge density, formations that make up the urban pattern were analyzed. Urban functional districts of different built-up density were separated using appropriate indexes, and extending the database with spectral content made it possible to review district boundaries and to mark new boundaries due to these changes.